RESEARCH METHODS FOR DIAGNOSING IKE COVID - 19 ON THE BACKGROUND OF PNEUMONIAAND - Safoev B.B; Turdiev H.K; Yarikulov Sh.Sh; Ubaidullaev B.B (Scholar Express Journals, 2022)
The COVID-19 viral infection, to which the WHO has assigned the category of a pandemic, is caused by a representative of a group of coronaviruses, which, in turn, belong to the family of seasonal SARS. The disease SARS-CoV-2, called COVID-19, was officially declared a pandemic by the World Health Organization on March 11, 2020. SARS-CoV-2 contains a single-stranded RNA genome with a positive meaning, surrounded by an extracellular membrane containing a series of spiked glycoproteins resembling a corona.
Keywords: COVID-19; SARS-CoV-2; covid-19